PENGEMBANGAN VIDEO ANIMASI BERBASIS PENGETAHUAN MITIGASI BENCANA BANJIR PADA ANAK USIA 5-6 TAHUN DI TK MUTIARA BUNDA KABUPATEN KAMPAR - Siti Ainun Nasution; Yeni Solfiah; Febrialismanto (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article discusses the development of a mitigation flood disaster knowledge-based animation video for children aged 5-6 years. Research and development of animated video media were conducted through analysis, design, development, implementation, and evaluation. The study was an R&D research using the ADDIE model developed by Robert Maribe Branch. Research development is the process or product steps that already existed and could be tested for feasibility. The study consisted of five phases, namely analysis, design, development, implementation, and evaluation. The results obtained indicated that the media assessment of validator I and validator II achieved an average percentage value of 90% with the category of decent. The results of the assessment from 5 educators achieved an average percentage value of 90% with the category of decent. And the results of the product trial carried out in a limited trial that was 6 children who were near the researcher's home was 92% with the category of decent. Data collection techniques used observation sheets and then were analyzed based on the obtained results.